(untitled) (American Journal of Pedagogical and Educational Research, 2023)
Fitness sports as part of physical culture of healthy lifestyle trainings serve to ensure the physical development of the population. It is organized by organizations and institutions that form the basis of ideological scientific-methodical, programmatic norms, as well as the physical culture of public health and control its level.